Pop-Up Book As A Health Education Media On Smoking Prevention For Elementary School Students: Pop-Up Book Sebagai Media Edukasi Kesehatan Pencegahan Merokok Bagi Siswa Sekolah Dasar - Chifdillah, Nino; Arnita, Firda; Bernadetha, Bernadetha; Rahayu, Eka Putri (Panakeia Journal of Epidemiology, 2025)
Smoking behavior and smoking-related diseases were global health problems. The prevalence of school-age child smokers in Samarinda city has increased in the last three years. The study aimed to analyze the effect of health education with pop-up book media on knowledge and motivation to prevent smoking in students of SDN 009 Loa Janan Ilir. The type of research was a pre-experimental study with a one group pretest-posttest design. Research intervention was applied through health education with pop-up book media. The research sample was amounted to 67 fifth-grade students of SDN 009 Loa Janan Ilir which determined by total sampling. Data were collected through questionnaires. The research data were tested statistically using the Wilcoxon test. The results showed that the number of students who had good knowledge increased by 47 people (70.1%) and positive motivation increased by 29 people (46.3%). The results of statistical analysis showed that there was an effect of pop-up book media health education on the knowledge (ρ-value = 0.000) and motivation of respondents (ρ-value = 0.002) about smoking prevention. Pop-up book media was effective as a health education media on smoking prevention for primary students.